PELATIHAN MENINGKATKAN KETERAMPILAN SISWA KELAS XI SMK BAZNAS SULSEL DALAM MELAKUKAN BANTUAN HIDUP DASAR - Sudarman Sudarman (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
This study aims to determine the effect of basic life support training on improving the skills of students of class XI Vocational High School Baznas Sulsel. This study uses a quantitative approach to the type of quasi-experimental research and research design pre and post test control group design. In this design the researcher intervened in two groups. The first group as the treatment group and the second group as the control group. The population in this study were all students of Vocational School Baznas Sulsel class XI, amounting to 42 people consisting of 21 intervention groups and 21 control groups. The test used by the Wilcoxon Test is to determine differences in skills before and after in the two groups. The results showed that there was an influence of basic life support training on the skills of Grade XI Students in the Vocational School of Baznas, South Sulawesi, with a value of α = 0.001 (<0.05). There is an effect of providing guidance on basic life assistance to the skills of Class XI Students in the Vocational School of Baznas South Sulawesi with a value of α = 0.008 (<0.05). There is a difference in skills between students who were given training and those who were not given basic life support for Class XI Students at the Vocational High School Baznas South Sulawesi with a value α = 0.015 (<0.05). The conclusion in this study is that there are differences in skills between students who are given training and those who are not given basic life support for Class XI Students at the Vocational High School Baznas South Sulawesi. It is expected that the manager of the Baznas Vocational High School in South Sulawesi needs to plan basic life support training, provide equipment / pantom pulmonary resuscitation, procedural basic video support and life support to improve the knowledge and skills of students and nurses in the Makassar city community need to conduct assistance training programs basic life for vocational high school